The Influence of The Brilink Financial Transaction System on Customer Satisfa (Study on The Brilink Agent in Liang Sub-District, Salahutu District, Central Maluku District) - Novita Hatuluayo; Kevin H. Tupamahu; Syahrina Noormala Dewi (Journal of Indonesian Science Economic Research, 2022)
Brilink agent is one of BRI’s service innovations, where BRI Bank cooperates with customers in the form of partnerships. The problem in this research is whether the brilink financial transaction system has an effect on customer satisfaction in the country of burrows.the purpose of This study is to investigate and analyze the effect of the brilink financial transaction system on customer satisfaction, especially based on the dimensions of brilink’s influence which consists of the following variables: benefits, convenience, and security on customer satisfaction at the brilink agent in liang country. This research is quantitative, using explanatory research method (explanatory research). data collection method is done by questionnaire, the sample in this study were 50 customers at the brilink agen in liang country twith a sampling technique that is purposive sampling. The analytical method used is multiple linear regression analysis using SPSS version 20 program. Based on the results of research with statistically multiple linear regression, the brilink financial transaction system which consisting of three dimensions of the financial transaction system, namely benefits, convenience, and security. brilink agent for the burrow country, salahutu sub-district, central Maluku district.